Collaborative evaluation of individual and team performance in training and match environments using the coach logic online platform - Vinson, D.; Beeching, K.; Morgan, M.; Jones, G. (International Sport Coaching Journal, 2017)
Sports coaches` commonly have a limited appreciation of pedagogy (Light & Evans, 2013). Furthermore, investigations concerning coaches` use of performance analysis for athlete learning are rare (Groom, Cushion, & Nelson, 2011). Complex Learning Theory (CLT) advocates nonlinear and sociocultural educative approaches (Light, 2013). Considering this digital age, the aim of this investigation was to examine coaches` use of Coach Logic—an online video-based coaching platform. Seven Head Coaches (five rugby union and two field hockey) were interviewed individually whilst their coaching staff and players contributed to group interviews. Results confirmed a priori themes of active, social and interpretive as derived from CLT. Analysis of these findings established that online coaching platforms have the capacity to facilitate the active involvement of athletes in the process of performance analysis. From a social perspective, online coaching platforms have helped to develop a positive team environment and also interpersonal working. Good practice was evident relating to interpretive approaches; however, the potential for coaches to embrace more radical conceptualisations of knowledge acquisition is stark. Online coaching platforms have a place in contemporary team sport environments and can contribute to athlete learning and other important aspects of team culture and cohesion.